HUBUNGAN ANTARA SELF-REGULATED LEARNING DAN INTENSI PENGGUNAAN MEDIA SOSIAL PADA REMAJA DI KOTA MEDAN - Wiwik Wahyuni; Asina Christina Rosito (LPPM Universitas HKBP Nommensen, 2021)
The purpose of this study was to determine whether there is a relationship between self-regulated learning and the intention to use social media among adolescents in Medan. The participants in this study were 275 teenagers in Medan. The data collection was carried out by distributing the self-regulated learning scale and the social media use intention scale, online using the google form. The data analysis technique used descriptive analysis in the form of categorization of self-regulatory learning scores and scores of intention to use social media. In order to test the hypothesis, the correlation analysis was conducted. The results showed that research participants with high self-regulated learning were 44.4% (n=122), while those with the medium category were 52% (n=143) and those with low categories were 3.6% (n=10). The research participants with the intention to use social media in the high category were 17.1% (n=47), in the medium category are 74.9% (n=206) and in the low category are 8.0 % (n=22). Based on the results of the correlation test, the correlation coefficient value was -0.064, with a significance level of 0.288 (p> 0.05). With these results, it means that there is no significant relationship between self-regulated learning and the intention to use social media in adolescents in Medan. Thus the hypothesis of this study was rejected. Further discussion of the results is presented